The Dialectics of Customary Law and Islamic Law: An Experience from Dou Donggo Customs of Bima, Indonesia - Muhammad Mutawali (AHKAM : Jurnal Ilmu Syariah, 2021)
This article aims to critically study the shift of Donggo Customs and traditions due to its dialectics with Islamic law. The Donggo customary law is based on the traditional practices and local wisdom of their ancestors that are believed to have noble values and truth. Since the 17th Century, the dialectics signified by the Bima kingdom’s political system changes from the old customs into Islamic law. This has influenced all aspects of the Bima  people’s live, including the Donggo community. This is qualitative research, with data from interviews and document studies. This study reveals that the Donggo Community’s customary law, preserved and practiced today, comes from the dialectics between customary law and Islamic law. The practiced traditions include baja sentence, the flogging law, the mbolo weki culture, maja labo dahu and raju ritual. In Islamic law, such traditions are called ‘urf or al-‘ādah, which are living traditions in a society used as legal sources and recognized by Islamic legal scholars. Customary law implemented by the Donggo indigenous people is considered substantially similar to Islamic teachings. So, Donggo customs, corresponding with the Islamic law (‘urf ṣaḥīh), are maintained, while the contradicting ones (‘urf fāsid) are abandoned.Abstrak:Artikel ini bertujuan untuk mengkaji secara kritis pergeseran adat dan tradisi Donggo sebagai proses dialektika dengan hukum Islam. Hukum adat Donggo didasarkan pada praktik tradisional dan kearifan lokal nenek moyang mereka, yang diyakini memiliki nilai-nilai luhur dan kebenaran. Sejak abad ke-17, dialektika yang ditandai dengan sistem politik kerajaan Bima berubah dari adat lama menjadi hukum Islam. Hal ini telah mempengaruhi seluruh aspek kehidupan masyarakat Bima, termasuk masyarakat Donggo. Jenis penelitian ini adalah kualitatif, dengan data dari wawancara dan studi dokumen. Kajian ini mengungkapkan bahwa hukum adat Masyarakat Donggo yang dilestarikan dan dipraktikkan hingga saat ini, merupakan hasil dari dialektika antara hukum adat dan hukum Islam. Tradisi yang dipraktikkan antara lain hukuman baja, hukum cambuk, budaya weki Mbolo, ritual Maja Labo dahu dan Raju. Dalam hukum Islam, tradisi semacam itu disebut `urf atau al-`adah, yaitu tradisi yang hidup dalam masyarakat yang dijadikan sumber hukum dan diakui oleh para sarjana hukum Islam. Adat atau hukum adat yang dilaksanakan oleh masyarakat adat Donggo secara substansi dianggap mirip dengan ajaran Islam. Jadi, adat Donggo yang sesuai dengan syariat Islam (`urf shahih) tetap dipertahankan, sedangkan yang bertentangan (`urf fasid) ditinggalkan.